Crowdassistant: a virtual buddy for crowd worker - Abhinav, Kumar; Dubey, Alpana; Jain, Sakshi; Bhatia, Gurpriya Kaur; McCartin, Blake; Bhardwaj, Nitish (2018 IEEE ACM 5th International Workshop on Crowd Sourcing in Software Engineering (CSI SE), 2018)
Crowdsourcing is an emerging practice which provides workers, across the globe, to work on their choice of tasks. It offers many benefits to people over traditional long term employment model, such as, schedule and geographic flexibility, easy access to work, an opportunity to gain experience on wide variety of tasks, or supplemental revenue streams. However, it also brings a new set of challenges to the workers. Workers on crowdsourcing platform do not have similar level of support as they get in traditional employment model, such as career guidance, compensation counseling, HR support, etc. To overcome the challenges crowd workers face, we propose "CrowdAssistant" which acts as a virtual buddy for the worker and helps them throughout their career journey on the platform. It even renders a level of support impossible for human managers and career counselors to provide. The proposed system acts as a personalized assistant and pro-actively supports worker's needs. It is the first of its kind to the best of our knowledge.